Physician-to-Nurse Handover: A Systematic Review on the Effectiveness of Different Models. Issue 1 (January 2022) - Odone, Anna; Bossi, Eleonora; Scardoni, Alessandro; Balzarini, Federica; Orlandi, Carlo; Arrigoni, Cristina; Signorelli, Carlo; Garancini, Paola
Abstract : Objectives: Effective professional communication and accurate transfer of relevant clinical information are crucial components of healthcare delivery. National and international health authorities strongly recommend the adoption of effective handover practice. Still, scant evidence is available on the impact of different multiprofessional handover models. Methods: We carried out a systematic review following the Prepared Items for Systematic Reviews and Meta-Analysis guidelines to retrieve, pool, and critically appraise the available evidence on the effectiveness of different physician-to-nurse handover models adopted in inpatient settings. Results: We identified 1.243 citations searching the databases Medline, Embase, and CINAHL. After screening, 10 studies were included in the review reporting results on the effectiveness of 8 different handover models, measured on 44 different outcomes, grouped into: (1) process of care and efficiency outcomes, (2) patients' outcomes, and (3) healthcare professionals–related outcomes. Overall, applying structured handover tools improve healthcare practice and selected outcomes; however, not only solid evidence on the effectiveness of different handover models is scant but also global consensus is lacking on which standardized measures and indicators to use to assess their impact. Conclusions: In times of healthcare delivery models of growing complexity, multiprofessional handover is a key component of care paths. Although there is overall consensus on the need for improving the quality and safety of multiprofessional handover, the evidence on the tools available to achieve it and the metrics to measure their impact is heterogeneous. We urge that rigorous studies are conducted to inform the planning, implementation, and monitoring of effective handover, with the ultimate aim of improving quality of care and patient safety. Abstract : Supplemental digital content is available in the text.